Surrogacy (Regulation) Act 2021 And The Right To Procreation In India (Journal of Pharmaceutical Negative Results, 2022)
Though motherhood completes a woman but it is not possible for every woman to embrace motherhood naturally. Infertility is a healthproblem faced by people across the world since time immemorial. With advancement of science and technology came the solutions forinfertility and specially with development of In Vitro Fertilization (IVF) technology came the solution to have one’s own child. WithIVF came in the concept of surrogacy, which finds a mention even in Bible and in Hindu Puranas. Due to low cost, less legislativecontrol and easy availability of surrogates, India became a hub for international surrogacy. As each side has two coins the boom insurrogacy came in with its own negative consequences and apprehensions of exploitation of the poor surrogates and moral argumentsagainst renting of womb. The Indian Legislature passed the new Surrogacy (Regulation) Act 2021, whereby India recently bannedcommercial surrogacy. Through the present research paper, the researcher aims to throw light on the legislative measures for surrogacyat the national and international level and aims to examine the scope of Right to reproduction in India. Through this research paperthe researcher aims to critically analyze the constitutional validity of Surrogacy (Regulation) Act 2021, in light of Article 21 of theIndian Constitution. The researcher has also discussed the responses generated through field research carried out by the researcher byinterviewing surrogates personally in Anand, Gujarat in the present research paper to evaluate the informed consent on the parts of thesurrogates while entering into surrogacy agreement.